Metagenomic DNA Library: Exploration of Novel Genes Encoding Glycoside Hydrolases - Kurniawati, Maris; ., Sudiyono; ., Purkan; Sumarsih, Sri; Baktir, Afaf (International Journal of Engineering and Technology, 2018)
Metagenomic is a potential approach to explore novel genes from a reservoir of genes. Metagenomic cDNA library as part of metagenomic approach be able to explore abundant quantity of microbiota genes. Metagenomic library collection was screened by functional and sequence analysis. Functional analysis can be done through induction genes expression substrat. Positive clones can be screened by expression of interest genes. Data of sequence analysis is very important in the process of product identification.Â Â